The Problems of Picture Media in Teaching Arabic Vocabulary in Kindergarten - Jimi, Harianto; Sulistianah, Sulistianah (CV. Creative Tugu Pena, 2024)
Kindergarten is a formal educational institution that is essentially a place to learn while playing. In accordance with the decision of the Minister of Education and Culture R[ No. 0125/J/1994 dated 16 May 1994 that the Kindergarten learning activity program aims to help lay the foundation for the development of attitudes, knowledge, skills, creativity and that students need to adapt to their environment, growth and further development. In achieving educational goals, the program of learning activities and basic ability development includes Creativity, Language, and Thinking power. Teaching Arabic in Kindergarten aims to provide foreign language provisions in a simple form, namely, mastery of language knowledge because understanding is very important. Plays an important role in foreign languages, especially in the Arabic language teaching and learning process. The quality of a person's language clearly depends on the quality and quantity of understanding he has. The more experience you have, the greater the possibility of being proficient in the language. The formulation of the problem in this research is: 1. To what extent is the understanding of learning Arabic using image media in TK IT Adzkia Al Husna in mastering Arabic vocabulary? 2. Is there a significant difference between the results of learning Arabic using image media and without using image media? After explaining all the experimental results in detail, at the end of the discussion of this research, the author can conclude as follows: Teaching Arabic, especially about vocabulary, using image media is more effective and efficient in improving students' mastery of Arabic at the IT Adzkia Al Husna Kindergarten, as evidenced by the average difference of 10.7368 for the experimental group and 2.4211 for the control group. There is a significant difference between the results of learning to understand Arabic using image media and regular teaching (without using image media). By using the